Powstanie, organizacja i zakres działania Dyrekcji Ceł w Poznaniu w latach 1918-1939 - Tamborski, Andrzej (Wydawnictwo DiG, 2014)
p. 3- 13 : ill.
Summary in German.
Contains tables.
Keywords: Dyrekcja Ceł, Poznań 1918-1939; public administration - Poland - Poznań (region) - history; customs administration - Poznań (Poland) 20yh c.

Przejęcie administracji celnej w województwie poznańskim w latach 1920–1921 - Institute of History of the Polish Academy of Sciences (Instytut Historii Polskiej Akademii Nauk, 2017)
Under article 256 of the Treaty of Versailles, the states to which German territory was ceded, acquired all property and possessions situated therein belonging to the German Empire or to the German States. The technical part of this resolution for the former Prussian partition was regulated mainly by the Polish-German Agreement ceding the civilian administration signed in Berlin on 25 November 1919. The taking over of the state customs properties, initiated in Poznań province in January 1920, was concluded by the end of January of the following year.
p. 205-227 ; Summary in English
Keywords: public finances - Poland - Wielkopolska (region); Poland - 1918-1939 (Second Polish Republic) - politics and government; Treaty of Versailles (1919); public administration - Poland - Poznań (region) - history; customs - Poland -1900-1945